ORDINARY CHONDRITE METALLOGRAPHY: PART 2. FORMATION OF ZONED AND UNZONED METAL PARTICLES IN RELATIVELY UNSHOCKED H, L, AND LL CHONDRITES - Reisener R.J.; Goldstein J.I. (My University, 2003)
We studied the metallography of Fe-Ni metal particles in 17 relatively unshocked ordinary chondrites and interpreted their microstructures using the results of P-free, Fe-Ni alloy cooling experiments (described in Reisener and Goldstein 2003). Two types of Fe-Ni metal particles were observed in the chondrites: zoned taenite + kamacite particles and zoneless plessite particles, which lack systematic Ni zoning and consist of tetrataenite in a kamacite matrix. Both types of metal particles formed during metamorphism in a parent body from homogeneous, P-poor taenite grains. The phase transformations during cooling from peak metamorphic temperatures were controlled by the presence or absence of grain boundaries in the taenite particles. Polycrystalline taenite particles transformed to zoned taenite + kamacite particles by kamacite nucleation at taenite/taenite grain boundaries during cooling. Monocrystalline taenite particles transformed to zoneless plessite particles by martensite formation and subsequent martensite decomposition to tetrataenite and kamacite during the same cooling process. The varying proportions of zoned taenite + kamacite particles and zoneless plessite particles in types 46 ordinary chondrites can be attributed to the conversion of polycrystalline taenite to monocrystalline taenite during metamorphism. Type 4 chondrites have no zoneless plessite particles because metamorphism was not intense enough to form monocrystalline taenite particles. Type 6 chondrites have larger and more abundant zoneless plessite particles than type 5 chondrites because intense metamorphism in type 6 chondrites generated more monocrystalline taenite particles. The distribution of zoneless plessite particles in ordinary chondrites is entirely consistent with our understanding of Fe-Ni alloy phase transformations during cooling. The distribution cannot be explained by hot accretion-autometamorphism, post-metamorphic brecciation, or shock processing.